THE RELATION OF MOTHERS' NUTRITIONAL STATUS TO PRIMARY TEETH DENTAL CARIES - Badruddin, Iwany Amalliah; Khansa, Muthia; Darwita, Risqa R; Rahardjo, Anton (International Journal of Applied Pharmaceutics, 2018)
Objective: According to the National Health Survey in 2013, nutritional problems in Indonesia are still a concern, and caries is the most prevalent dental disease. Primary dentition is developed during a mother's pregnancy period. Thus, mothers' nutritional status during pregnancy could determine the health of their children's primary dentition. This study objective was to analyze the relationship between mothers' nutritional status and dental caries in their children's primary teeth. Methods: In total, 281 children under 5-year-old were selected from a health screening in Depok Sub-District, West Java. Information about maternal nutritional status was collected through the mother and child's health book. Information about dental caries was collected through clinical examinations using the dmft index. Result: The prevalence of mothers with poor nutritional status was 22.8%, and 55.2% of their children had caries. The occurrence of dental caries in primary dentition between children of mothers with poor and good nutritional status was significantly different (p<0.001). The likelihood of getting caries was 1.85 times higher (95% confidence interval: 1.5–2.2) among children of mothers with poor nutritional status than among children of mothers with a good nutritional status. Conclusion: Children of mothers with a poor nutritional status would likely present with dental caries and had a higher risk of dental caries compared to children of mothers with a good nutritional status.